Analysis of Water Power Potential of the Suplesi Gebong Irrigation River for Power Plant Planning in the Village of Peresak Narmada Sub-Distric West Lombok District (J-AGENT (Journal of Agricultural Engineering and Technology), 2024)
The research is about Analysis of Water Power Potential of the Suplesi Gebong Irrigation River for Power Plant Planning in The Village of Peresak Narmada Sub-Distric West Lombok District. The purpose of this research was to analyze the availability of Suplesi Gebong irrigation river, to determine availability of electrical energy output of Suplesi Gebong irrigation river, and to determine the sort of power plant based on energy output. This research was conducted by using experimental method by collecting data from the field. Observed parameter in this research was obtained by measuring depth and width of the river, flow velocity to achieved flow rate, and elevation measurement on upstream and downstream part of the location. Flow rate and head data was acquaried to calculate potential power. Based on the results of the research, it could be determined that the effective head was 0.9 m and value of obtained flow rate is in the range of 0,33 mÂ³/s to 0,58 mÂ³/s. Potential output power based on flow rate and head value was 2,91 kW to 5,12 kW and could be prerequirement as Pico Hydro and Micro Hydro Power Plant (MHPP).
Keywords: potency of hydropower; flow rate; head; micro hydro power plant (MHPP)